The Role of Arabic Language Learning in the Development and Understanding of Hadith Science - Burhanuddin, Burhanuddin; Muhammad Rezky Ramadhan; Davinna Sherenia Pramesti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Arabic plays a central role in the Islamic world as the language of the holy scriptures of the Qur'an and Hadith, the language of religion, the official language of the United Nations (UN), and the national language in over 25 countries in the Middle East. Additionally, Arabic is known as